Developing science, mathematics, and ICT education in Sub-Saharan Africa : patterns and promising practices - Ottevanger, Wout (World Bank working paper ;, 2007)
This working paper is based on a literature review and country case studies from ten Sub-Saharan African countries: Botswana, Burkina Faso, Ghana, Namibia, Nigeria, Senegal, South Africa, Uganda, Tanzania and Zimbabwe. It reveals a number of huge challenges in science, mathematics, and ICT education (SMICT) in sub-Saharan Africa: poorly-resourcedschools; large classes; a curriculum hardly relevant to the daily lives of students; a lack of qualified teachers; and inadequate teacher education programs. Through examining country case studies, this paper discusses the lessons for improvement of SMI.